2024
DOI: 10.1002/cpe.8019
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time XFEL data analysis at SLAC and NERSC: A trial run of nascent exascale experimental data analysis

Johannes P. Blaschke,
Aaron S. Brewster,
Daniel W. Paley
et al.

Abstract: SummaryX‐ray scattering experiments using free electron lasers (XFELs) are a powerful tool to determine the molecular structure and function of unknown samples (such as COVID‐19 viral proteins). XFEL experiments are a challenge to computing in two ways: (i) due to the high cost of running XFELs, a fast turnaround time from data acquisition to data analysis is essential to make informed decisions on experimental protocols; (ii) data‐collection rates are growing exponentially, requiring new scalable algorithms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The Linac Coherent Light Source (LCLS) at SLAC National Accelerator Laboratory provides X-ray scattering for the study of the molecular structure and function properties of materials and substances. Past work [2] has demonstrated a scientific workflow that forwards experiment data from LCLS to the National Energy Research Scientific Center (NERSC) at Lawrence Berkeley National Laboratory (LBL) to provide quick data analysis that enables scientists to make informed decisions when configuring subsequent experiment runs. The existing workflow uses file-based transfers of experimental image data from the SLAC analysis file system to NERSC shared storage systems, using a clustered data transfer service known as XRootD that runs at both sites.…”
Section: Slac Lclsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Linac Coherent Light Source (LCLS) at SLAC National Accelerator Laboratory provides X-ray scattering for the study of the molecular structure and function properties of materials and substances. Past work [2] has demonstrated a scientific workflow that forwards experiment data from LCLS to the National Energy Research Scientific Center (NERSC) at Lawrence Berkeley National Laboratory (LBL) to provide quick data analysis that enables scientists to make informed decisions when configuring subsequent experiment runs. The existing workflow uses file-based transfers of experimental image data from the SLAC analysis file system to NERSC shared storage systems, using a clustered data transfer service known as XRootD that runs at both sites.…”
Section: Slac Lclsmentioning
confidence: 99%
“…For this capability we want to focus on memory-to-memory data movement (i.e., moving data directly from the memory of producer applications to the memory of consumer applications) and avoid requiring data transfers between file systems as the basis for moving data between experimental and HPC systems. File-based data movement is already well-supported by the U. S. Department of Energy (DOE) Advanced Scientific Computing Research (ASCR) user facilities and has been shown to be a bottleneck for certain use cases [2,20].…”
Section: Introductionmentioning
confidence: 99%